Semiotics for Interpreting Quilt’s Cultural Values from the U.S. and Indonesia - Ekawati Marhaenny Dukut (k@ta: A Biannual Publication on the Study of Languange and Literature, 2018)
Historically, quilt making has been recorded in the United States (U.S.) since the 18th century not only for its function but for the social expression of its people to their environment. The different colors and symbols used in designing and making quilts give knowledge to what quilt creators want to express. By use of library research and semiotics for an analytical-descriptive discussion, the socio-cultural and historical perspectives of U.S. quilts are found to explain how designs have evolved from the 18th to the 21st century of the U.S. The semiotics method has also shown how through an American Studies transnational process of cross bordering countries, the U.S. quilt has influenced its neighboring countries, like Indonesia. This article shares how a number of U.S. quilt patterns, colors and cultural values are found in Indonesian quilt. Among the cultural values found are the maintenance of loyalty and obedience. Interestingly, while the U.S. cultural value of individualism is respected, the Indonesian collectivism is preferred more in quilt making.